Seleucia on the Tigris. New Observations on the Landscape and City Layout - Foietta, Enrico; Lippolis, Carlo; Messina, Vito (Anabasis. Studia Classica et Orientalia, 2022)
This study makes available observations on the landscape and urban layout of Seleucia on the Tigris, to present fresh insights by thematic maps and digital models. These are based on the cross-analysis of different data, acquired by ground survey, historical documents and remote sensing to particularly address preliminary reconstructions of the waterways’ system and settlement patterns of the city and the area in which it is located.